Promoting Sustainable Products: Community Engagement and Eco-Friendly Practices at Namira Ecoprint in Surabaya - Evanthi, Ayundha; Ilham Hardi (Asian Journal of Community Services, 2024)
The growing global concern for sustainability is particularly acute in the fashion industry, often viewed as a major contributor to environmental degradation. In response, eco-green products emerged, prioritizing sustainable practices and minimizing harm to the environment. To effectively market these products, it's crucial to enhance knowledge and skills in eco-green marketing. This community service program at Namira Ecoprint Surabaya aims to combine sustainability with effective marketing, raising consumer awareness about eco-friendly products and their benefits. This community service program has successfully raised awareness and understanding of effective marketing strategies, the advantages of sustainable products, and how eco-friendly products can stand out.